La reprise comme ressource interactionnelle en langue seconde - Pochon-Berger, Evelyne (My University, 2008)
It is a well known fact that L2 learners encounter a variety of difficulties when participating in dynamic verbal exchanges in L2. Especially launching their turn in time, while dealing with formulation issues, proves to be difficult. Not only do they have to identify the precise moment for taking a turn, they also have to establish coherence with previous talk. This article focuses on other-repetition as interactional resource used by intermediate L2 learners in order to organize their turns-at-talk. On the basis of French L2 data and following a micro-analytical approach, two functions of other-repetition in L2 interactions will be illustrated: 1) as a turn expansion device and 2) as a turn entry device. The corpus consists of videotaped peer-group interactions within French L2 classroom setting.